The Factors Influencing Farmers’ Adoption of Agricultural Technology Innovations in Pacitan Agricultural Technology Park, East Java, Indonesia - Romadi, Ugik; Yastutik; Finunda, Olia Fitra (Jurnal Penyuluhan, 2025)
Agricultural Technology Park Pacitan is a venue that showcases innovations developed in Pacitan for farmers in the region. Based on data from the Agricultural Technology Park Pacitan, the interest of farmers in adopting innovations offered by the Park is very low. Moreover, it can be observed from the continued use of conventional farming patterns by some individuals. This study aims to describe the role of the Agricultural Technology Park Pacitan for farmers, and analyze the factors that influence farmer adoption of agricultural technology innovations in the Agricultural Technology Park Pacitan. The research method employed was a descriptive quantitative approach. Determination of the number of samples using the saturated sampling method was 43 respondents. The results revealed that the Agricultural Technology Park Pacitan needs to socialize innovations developed for farmers in the Pacitan Regency area, as well as those around it. Furthermore, the Agricultural Technology Park in Pacitan also serves as a forum for pilots to develop agricultural technologies that farmers can utilize. The factors that influence the level of adoption of agricultural technology innovations at the Agricultural Technology Park Pacitan are the type of innovation, methods, media, frequency of extension, perceived benefits, and suitability for needs.